SAT0652 Clinical and immunological significance of radiographic thymic alterations in patients with rheumatoid arthritis. (15th June 2017) - Murata, O; Suzuki, K; Sugiura, H; Kondo, Y; Takeshita, M; Yasuoka, H; Yamaoka, K; Koga, K; Morita, R; Yoshimura, A; Takeuchi, T
Abstract : Background: The thymus, a primary lymphoid organ, plays a crucial role in immune system homeostasis [1, 2]. Although several small-scale studies of the association between radiographic thymus alterations and serological features have been reported in systemic autoimmune diseases, information in patients with rheumatoid arthritis (RA) is limited. Objectives: We conducted a large-scale cross-sectional analysis of radiographic thymus alterations and their association with clinical and immunological features in patients with RA. Methods: RA patients were randomly selected from all patients who visited our department and underwent chest CT scan between January 2013 and December 2015. Patients with thymoma or thymic cyst and those aged less than 30 years were excluded. Thymic enlargement and thymus attenuation score in axial images of CT scans were quantitatively interpreted. We defined thymic enlargement as a thickness of more than 13 mm and graded the score by a four-point scale (score 0–3) according to previous studies [3, 4]. Associations with immunophenotyping data of peripheral blood by flow cytometry and clinical and serological information were statistically analyzed in some available patients. Results: 387 RA patients were enrolled. 78% were women and mean age was 65.2±12.3 years. Thymic enlargement was found in 76 (19.6%) patients. Thymus attenuation (score ≥2) was found in 154 (39.8%) patients. These findings were more frequent than in undiagnosed controls (11.3% ( P =0.078) and 22.5% ( P =0.017)). Importantly, radiographic thymus alterations in these RA patients, especially thymus attenuation score, were significantly associated with serological features such as serum level of CRP, ESR, IgG, RF-positivity or ACPA-positivity ( P =0.0003, 0.001, 0.0009, 0.005, and 0.0009 respectively). When we investigated the association with the proportion of 68 peripheral blood subpopulations in 83 RA patients, thymic enlargement was significantly associated with the proportions of CD45RA+CCR7+ naïve CD4+T cell or CD45RO+CCR7-effector memory CD4+T cell ( P =0.04 and 0.009). Furthermore, thymus attenuation score was also significantly associated with the proportions of CD4+ naïve T cell, CD4+effector memory T cell, CXCR5-CXCR3+CXCR6+CD4+Th1/Th17 cell, CD45RO-CCR7+CD95+CD4+ stem cell memory T cell, and CD19+ B cell ( P =0.03, 0.02, 0.04, 0.04, and 0.037 respectively). Conclusions: Radiographic thymus alterations are frequent in RA patients and may reflect immunological features of autoantibody production or T cell differentiation and function. References: Gorozny JJ, et al. Trends Immunol 2001;22:251–255. Seddon B, et al. Immunol Today 2000;21:94–99. Naidich P, et al. Lippincott-Raven 1999:57–73. Ackman JB, et al. Radiology 2013;268(1):245–253. Disclosure of Interest: None declared